EVALUASI PROGRAM PENINGKATAN KUALIFIKASI S1 GURU MADRASAH DAN GURU PAI MELALUI DUAL MODE SYSTEM (DMS) KEMENTERIAN AGAMA REPUBLIK INDONESIA DI LPTK RAYON 210 IAIN MATARAM - Abdul Fattah (Jurnal Madania)
The Evaluation of S1-Qualification Improvement Program for Teachers of Madrasah and PAI through Dual Mode System at the Ministry of Religious Affairs in LPTK Rayon 210 IAIN Mataram. The focus of this study is to examine the effectiveness of S1-Qualification Improvement program for the teachers of Madrasah and PAI through Dual Mode System (DMS) at the Ministry of Religious Affairs, for the region of West Nusa Tenggara, East Nusa Tenggara, and Bali in LPTK Rayon 210 IAIN Mataram. The specified targets are reviewed from five components including context, input, process, product, and impact (output) or outcomes. The model of research design used in this study is CIPP Stufflebeam’s evaluation model by adding outcome (O) components so that it becomes a CIPPO model. Generally, it is concluded that the implementation of the S1-Qualification Improvement program through Dual Mode System (DMS) in LPTK Rayon 210 IAIN Mataram has been going well and in accordance with the guideline and rule standard set by the Ministry of Religious Affairs Republic Indonesia, although there are some aspects needed to be repaired and increased